2016
DOI: 10.1016/j.cels.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Cell Transcriptomic Map of the Human and Mouse Pancreas Reveals Inter- and Intra-cell Population Structure

Abstract: Summary Although the function of the mammalian pancreas hinges on complex interactions of distinct cell types, gene expression profiles have primarily been described with bulk mixtures. Here we implemented a droplet-based, single-cell RNA-seq method to determine the transcriptomes of over 12,000 individual pancreatic cells from four human donors and two mouse strains. Cells could be divided into 15 clusters that matched previously characterized cell types: all endocrine cell types, including rare epsilon-cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
1,391
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 1,280 publications
(1,538 citation statements)
references
References 64 publications
71
1,391
4
4
Order By: Relevance
“…Application of k-nearest neighbor smoothing to scRNA-Seq data from human pancreatic islet tissue. All panels show data from the PANCREAS dataset, from a study by Baron et al (2016). Smoothing was performed using k = 15. a Principal component analysis (PCA) with (top) and without (bottom) smoothing.…”
Section: /33mentioning
confidence: 99%
See 2 more Smart Citations
“…Application of k-nearest neighbor smoothing to scRNA-Seq data from human pancreatic islet tissue. All panels show data from the PANCREAS dataset, from a study by Baron et al (2016). Smoothing was performed using k = 15. a Principal component analysis (PCA) with (top) and without (bottom) smoothing.…”
Section: /33mentioning
confidence: 99%
“…Axis labels indicate the fraction of variance explained. Cell types were identified based on the smoothed data, using ad-hoc expression thresholds for the marker genes listed in Baron et al (2016). Beta cells were defined as having expression of INS ≥ 40,000 TPM (UMI-filtered transcripts per million); alpha cells, GCG ≥ 5,000 TPM; delta cells, SST ≥ 20,000 TPM; acinar cells, CPA1 ≥ 1,000 TPM.…”
Section: /33mentioning
confidence: 99%
See 1 more Smart Citation
“…However, other more complex organs such as the brain do not exhibit a corresponding number of 15 expressed genes despite the fact that they consist of a substantially greater number of distinct cell types 3,10, [14][15][16] . Moreover, recent animal studies have shown that many testis-enriched and evolutionarily-conserved genes are not required for male fertility in mice 17 .…”
Section: Main Textmentioning
confidence: 99%
“…For example, Baron et al has successfully implemented InDrops to compare the single cell transcriptome between mouse and human pancreas. 32 Briggs et al applied inDrops to compare motor neurons generated by two differentiation protocols and revealed that mature cell state can be reached via multiple differentiation paths. 33 …”
Section: Microfluidic Based Scrna-seqmentioning
confidence: 99%